3.8k views
0 votes
This question is confusing. Please help me!This question is confusing. Please help me!

This question is confusing. Please help me!This question is confusing. Please help-example-1

2 Answers

2 votes

Answer:

C

Explanation:

We are given

t + 3t + 2 = s + 3s, that is

4t + 2 = 4s ( subtract 4t from both sides )

2 = 4s - 4t ← factor out 4 from each term

2 = 4(s - t) ← divide both sides by 4 , thus

s - t =
(2)/(4) =
(1)/(2) → C

User Willman
by
5.7k points
1 vote

Answer:

(C) 1/2

Explanation:

  • s + 3s = 4s
  • t + 3t = 4t

If 4s is 2 more than 4t, then:

  • 4s = 2+ 4t
  • 4s - 4t = 2
  • 4s/4 - 4t/4 = 2/4
  • s - t = 1/2

(C) is the answer

User Robotshapes
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.